Evidence-based classification in powerchair football: determining the determinants - Barfield, J.P.; Williams, S.; Currie, M. R.; Guo, X. (Adapted Physical Activity Quarterly, 2023)
The purpose of this study was to initiate the development of an evidence-based sport classification system for powerchair football, a sport that serves athletes with physical impairments. Sport classification is designed to increase participation by minimizing the impact of impairment on competition outcome, and powerchair football lacks an evidence-based system of classification which is required of Paralympic sports. A number of approaches were used to build the theoretical model of sport performance (Step 2 of the International Paralympic Committee model). Key sport activities were identified through surveys of stakeholders and underlying determinants of those key activities were identified through game and database analyses. Current findings support drive control, ball control, communication, and adjustment to the ball as key activities in powerchair football with joint-specific strength and range of motion, sensory, and neurological variables identified as underlying determinants.